Targeting hedgehog-driven mechanisms of drug-resistant cancers - Miller, Jade S.; Bennett, Natalie E.; Rhoades, Julie A. (Frontiers in Molecular Biosciences, 2023)
Due to the cellular plasticity that is inherent to cancer, the acquisition of resistance to therapy remains one of the biggest obstacles to patient care. In many patients, the surviving cancer cell subpopulation goes on to proliferate or metastasize, often as the result of dramatically altered cell signaling and transcriptional pathways. A notable example is the Hedgehog (Hh) signaling pathway, which is a driver of several cancer subtypes and aberrantly activated in a wide range of malignancies in response to therapy. This review will summarize the field's current understanding of the many roles played by Hh signaling in drug resistance and will include topics such as non-canonical activation of Gli proteins, amplification of genes which promote tolerance to chemotherapy, the use of hedgehogtargeted drugs and tool compounds, and remaining gaps in our knowledge of the transcriptional mechanisms at play.